The Waqf as The Social Institution and The Realization of Islam Nusantara: The Study in West Sumatera - Medaline, Onny (LPPM IAIN Kudus, 2018)
As a religion which concerned with the social, cultural, psychological and spiritual of the community, Islamic laws had the ability to answer the new problems, especially in all muamalah fields. The Islamic of Nusantara was the comprehension, experience, and implementation of Islam in mualamat of fiqih segment as the dialectical result among the syariat, cultural and reality throughout the archipelago. The reality reflected on in waqf that became a dynamical ijtihadiyyat laws along with the benefit which fulfilled the certain space, time and situation. The waqf as the social institution was the realization of the Islamic laws transformation to become a law formation which consisted of the funding system of tasawuf (ilahiyah) study and Islam absolute which grew as the social framework that had the ability to answer all the community needs in some of life fields which affected by the dynamic of space and time. In the context of social institution, the waqf was the norm system which arranged all the human actions in order to fulfill the basic needs in community life, and it was a part of community norms which formed the social, religion institutions and the other institutions which protected by the state.